A bibliometric analysis-based review on green IT - Nau, S Zaung; Marinova, Dora (Springer, 2020)
With the increasing global greenhouse gas emission (GHGE) from ICT usage, several research projects have been conducted in the areas for Green IT development (such as optimal resource allocation algorithms, deterministic heuristics approaches) and Green IT deployment (integrated framework approach). Although there was significant progress in Green IT research during the period of 2008–2013, it has declined gradually in recent years. The findings from all of these Green IT research play a vital role in improving the resource optimisation, which can result in GHGE from ICT usage. This book chapter presents the findings from bibliometric analysis, co-authorship and citation network analysis on Green IT articles. The findings show that the numbers of total related articles increased from 2008 to 2013 and gradually decreased in recent years. USA, Germany, India, Australia and England are the leading countries. The high average citations of articles from Australian scholars reflect their significant academic value in this Green IT research area, although the funding support from Australia research council on Green IT is comparatively low. There is a need to encourage more academic collaborations with co-authorship to share experiences, knowledge and skills for more innovative solutions. The citations among articles from worldwide are widely distributed and well linked among articles from various countries and academic institutions.